The odd terms and even terms are connected to each other here for instance the 4th term (16) is

(2nd term * 2) + (1st term) = 4th term

ie.,

**(7*2) + 2 = 16.**

similarly 5th term is

(3rd term*2)+(2nd term)

**(13*2)+(7) = 33.**

similarly 6th term is

(4th term*2)+(3rd term)

**(16*2)+(13) = 45.**

similarly 7th term is

(5th term*2)+(4th term)

**(33*2)+(16) = 82.**

And finally the required term

(6th term*2)+(5th term)

**(45*2)+(33) = 123.**

P.S> I don't know how 7 and 13 came to being going by this idea.